The effect of non-optimal lipids on the progression of coronary artery calcification in statin-naïve young adults: results from KOICA registry - Lee, Heesun; Ahn, Hyo-Jeong; Park, Hyo Eun; Han, Donghee; Chang, Hyuk-Jae; Chun, Eun Ju; Han, Hae-Won; Sung, Jidong; Jung, Hae Ok; Choi, Su-Yeon (Frontiers in Cardiovascular Medicine, 2023)
Background Despite the importance of attaining optimal lipid levels from a young age to secure long-term cardiovascular health, the detailed impact of non-optimal lipid levels in young adults on coronary artery calcification (CAC) is not fully explored. We sought to investigate the risk of CAC progression as per lipid profiles and to demonstrate lipid optimality in young adults. Methods From the KOrea Initiative on Coronary Artery calcification (KOICA) registry that was established in six large volume healthcare centers in Korea, 2,940 statin-naïve participants aged 20–45 years who underwent serial coronary calcium scans for routine health check-ups between 2002 and 2017 were included. The study outcome was CAC progression, which was assessed by the square root method. The risk of CAC progression was analyzed according to the lipid optimality and each lipid parameter. Results In this retrospective cohort (mean age, 41.3 years; men 82.4%), 477 participants (16.2%) had an optimal lipid profile, defined as triglycerides <150 mg/dl, LDL cholesterol <100 mg/dl, and HDL cholesterol >60 mg/dl. During follow-up (median, 39.7 months), CAC progression was observed in 434 participants (14.8%), and more frequent in the non-optimal lipid group (16.5% vs. 5.7%; p < 0.001). Non-optimal lipids independently increased the risk of CAC progression [adjusted hazard ratio (aHR), 1.97; p = 0.025], in a dose-dependent manner. Even in relatively low-risk participants with an initial calcium score of zero (aHR, 2.13; p = 0.014), in their 20 s or 30 s (aHR 2.15; p = 0.041), and without other risk factors (aHR 1.45; p = 0.038), similar results were demonstrable. High triglycerides had the greatest impact on CAC progression in this young adult population. Conclusion Non-optimal lipid levels were significantly associated with the risk of CAC progression in young adults, even at low-risk. Screening and intervention for non-optimal lipid levels, particularly triglycerides, from an early age might be of clinical value.